Insect pests and natural enemies associated with lettuce Lactuca sativa L. (Asteraceae) in an aquaponics system - da Silva, Tamara Machado; Cividanes, Francisco Jorge; Salles, Fernando André; Pacífico Manfrim Perticarrari, Amanda Liz [UNESP]; Zambon da Cunha, Suzan Beatriz; Monteiro dos Santos-Cividanes, Terezinha (Springer Nature, 2024)
Although food is produced in aquaponics systems worldwide, no information is available on the occurrence of insect pests and natural enemies in aquaponic lettuce, Lactuca sativa L. In this study, a survey was carried out in an aquaponic system combining lettuce with lambari, Astyanax altiparanae (Garutti & Briski), aiming to determine the insect pests and natural enemies associated with this system. We also determined the predominant insect species and the effect of meteorological factors on their populations. Insect abundance was estimated by visual sampling during 13 cultivation cycles, totaling 27 sampling dates. The meteorological factors considered were air temperature and relative humidity, and their effects were determined using the Pearson correlation. The thrips Frankliniella schultzei (Trybom) and Caliothrips phaseoli (Hood) and the aphid Aphis spiraecola (Patch) predominated. Ambient temperature and relative humidity were essential factors affecting C. phaseoli and F. schultzei. The natural enemies found on the lettuce plants were the thrips Franklinothrips vespiformis (Crawford) and Stomatothrips angustipennis (Hood) and the ladybugs Cycloneda sanguinea L., Eriopis connexa (Germar), and Hippodamia convergens (Guérin-Méneville). These results constitute the first step for a lettuce-integrated pest-management program in aquaponics systems.
Keywords: Aphid; Aquaponics; Ladybug; Predator; Thrips; Vegetable